Advanced patient age at diagnosis of diffuse large B-cell lymphoma is associated with molecular characteristics including ABC-subtype and high expression of MYC. Issue 5 (4th May 2018) - Paul, Ulrike; Richter, Julia; Stuhlmann-Laiesz, Christiane; Kreuz, Markus; Nagel, Inga; Horn, Heike; Staiger, Annette M.; Aukema, Sietse M.; Hummel, Michael; Ott, German; Spang, Rainer; Rosenwald, Andreas; et al.
Abstract: The incidence of diffuse large B-cell lymphoma (DLBCL) increases with age being patient age at diagnosis an adverse prognostic factor. However, elderly patients are often underrepresented in common studies. To investigate the effect between age and biological characteristics in DLBCL, we analyzed data of 1534 patients encompassing all adult age groups, enriched for the age ≥75 years. Follicular lymphoma (FL) grade 3B with histopathological characteristics of DLBCLs were included. Gender, centroblastic cytology, FL grade 3B morphology, CD10 expression, and ABC/non-GCB-subtype were significantly associated with age after correction for multiple testing and after adjusting for cohorts. Analysis of a subgroup points towards an association of MYC expression with age. Our data indicate that biological features of DLBCL and FL grade 3B are associated with increasing age among adult patients. The prevalence of the ABC/non-GCB-subtype in elderly patients suggests that therapies targeting this molecular subtype should be specifically explored in this subgroup.